SoxC is Required for Ecdysteroid Induction of Neuropeptide Genes During Insect Eclosion - Luo, Guang-Hua; Chen, Xi-En; Jiao, Yao-Yu; Zhu, Guan-Heng; Zhang, Ru; Dhandapani, Ramesh Kumar; Fang, Ji-Chao; Palli, Subba Reddy (Frontiers in Genetics, 2022)
In insects, the shedding of the old exoskeleton is accomplished through ecdysis which is typically followed by the expansion and tanning of the new cuticle. Four neuropeptides, eclosion hormone (EH), ecdysis triggering hormone (ETH), crustacean cardioactive peptide (CCAP) and bursicon (Bur) are known to control ecdysis. However, the regulation of these neuropeptide genes is still poorly understood. Here, we report that in the red flour beetle (RFB) Tribolium castaneum and the fall armyworm (FAW) Spodoptera frugiperda, knockdown or knockout of the SoxC gene caused eclosion defects. The expansion and tanning of wings were not complete. In both RFB and FAW, the knockdown or knockout of SoxC resulted in a decrease in the expression of EH gene. Electrophoretic mobility shift assays revealed that the SfSoxC protein directly binds to a motif present in the promoter of SfEH. The luciferase reporter assays in Sf9 cells confirmed these results. These data suggest that transcription factor SoxC plays a key role in ecdysteroid induction of genes coding for neuropeptides such as EH involved in the regulation of insect eclosion.